Marketing System of Grain from Farmers to Rice Mill Producers in Pringsewu District - Nurpalina Nurpalina; Irmayani Noer; Henry Kurniawan (AIBPM Publisher, 2022)
ABSTRACTÂ This article aims to identify the pattern of the grain/rice marketing system from the farmer-producing level to the milling producer and the activities carried out by the actors involved. Data collection was carried out in the rice production center area in Pringsewu Regency, namely Gadingrejo District because it has the largest rice area in Pringsewu Regency. Data were collected using survey methods (field observations) and interviews with producer farmers and actors involved in the grain/rice trade chain system in Pringsewu Regency. Respondents are rice farmers in Pekon Parerejo totaling 67 farmers, rice milling producers (huller) as many as 4 industries, and 2 collectors traders who are in the research location. Based on the results of the study, it was found that the pattern of the grain/rice trade system in Pringsewu Regency has a flow structure from the Pekon Parerejo production center, Gading Rejo District to several rice milling industries in Pringsewu Regency. There are two patterns, namely the first channel, farmers sell grain to traders and then to wholesalers, grain traders are collected and distributed on a large scale to hullers (mills). From the huller, the grain undergoes processing including drying, milling, grading and rice. The packaged and labeled rice is then distributed to wholesalers. From wholesalers distributed to retailers to be sold to consumers.Keywords: Marketing System,Â Â Channel of Marketing System, Actors an Activity